Caracterización del sub-suelo con tomografía eléctrica en una zona de la sede usme de la Universidad Antonio Nariño. (2022)
The Antonio Nariño University (UAN) proposes within its engineering plans the construction of a "Technological Park" in the Usme headquarters of said institution, although there are a series of previous studies of soils, a set of gaps are also located on the which detailed information on the composition of the soil is not available. In this way, the option of carrying out a deeper investigation is proposed in order to have a broader knowledge of the types of soils present in this location, considering the above, the proposal consists of carrying out the characterization of a specific area within the university using the application of a geophysical method known as "subsoil electrical resistivity test" as a complement to conventional tests insofar as soil characterization studies are concerned